Introduction of Avian metapneumovirus subtype A to the United States: molecular insights and implications - Goraichuk, Iryna V.; Torchetti, Mia K.; Killian, Mary L.; Kapczynski, Darrell R.; Sary, Kathleen; Kulkarni, Arun; Suarez, David L. (Frontiers in Microbiology, 2024)
Avian metapneumovirus (aMPV) poses a significant threat to the poultry industry worldwide, primarily affecting turkeys and chickens. The recent detection of aMPV-A and -B subtypes in the United States marks a significant shift after a prolonged period free of aMPV following the eradication of the previously circulating subtype C. Hence, the demand for molecular diagnostic tests for aMPV has arisen due to their limited availability in the US market. In this study, we present the molecular characterization based on the complete genome sequence of aMPV subtype A, which was detected in the US for the first time. Four RT-qPCR positive samples were subjected to next-generation sequencing analysis, resulting in the assembly of one complete and one near-complete genome sequences. Phylogenetic analysis revealed that the isolated strains clustered within the aMPV-A subtype and were most closely related to recent Mexican strains. A detailed amino acid analysis identified unique mutations in the G gene of the US isolates compared to Mexican strains. Additionally, we compared the performance, cross-reactivity, and limit of detection of our revised aMPV subtype-specific RT-qPCR test with two commercial kits, demonstrating similar detection and subtyping capabilities. These findings highlight the importance of accurate diagnostic methods for disease management in the poultry industry, provide valuable insights into the epidemiology of aMPV, and underscore the need for continued vigilance and surveillance to mitigate its impact on poultry production.